Novel progesterone receptors: neural localization and possible functions - Petersen, Sandra L.; Intlekofer, Karlie A.; Moura-Conlon, Paula J.; Brewer, Daniel N.; del Pino Sans, Javier; Lopez, Justin A. (Frontiers in Neuroscience, 2013)
Progesterone (P4) regulates a wide range of neural functions and likely acts through multiple receptors. Over the past 30 years, most studies investigating neural effects of P4 focused on genomic and non-genomic actions of the classical progestin receptor (PGR). More recently the focus has widened to include two groups of non-classical P4 signaling molecules. Members of the Class II progestin and adipoQ receptor (PAQR) family are called membrane progestin receptors (mPRs) and include: mPRα (PAQR7), mPRβ (PAQR8), mPRγ (PAQR5), mPRδ (PAQR6) and mPRε (PAQR9). Members of the b5-like heme/steroid-binding protein family include progesterone receptor membrane component 1 (PGRMC1), PGRMC2, neudesin and neuferricin. Results of our recent mapping studies show that members of the PGRMC1/S2R family, but not mPRs, are quite abundant in forebrain structures important for neuroendocrine regulation and other non-genomic effects of P4. Herein we describe the structures, neuroanatomical localization and signaling mechanisms of these molecules. We also discuss possible roles for Pgrmc1/S2R in gonadotropin release, feminine sexual behaviors, fluid balance and neuroprotection, as well as catamenial epilepsy.